Infraestrutura verde como prática sustentável para subsidiar a elaboração de planos de drenagem urbana: estudo de caso da cidade de Tupã/SP - Benini, Sandra Medina [UNESP] (2015)
This thesis discusses the importance of green infrastructure as a sustainable practice designed to underlie the development of urban drainage plans. For this, it was proposed to introduce a new look at the urban green, through theoretical and practical ground, in which was demonstrated the possibility of optimizing these spaces, through combined ecological processes (green and blue system, which are materialized through the use of the different kinds of typology of green infrastructure. Therefore, in addition to social, cultural, recreational (leisure) and environmental values to be explored in green spaces, this thesis presented the functional value of the types of green infrastructure applied to the urban stormwater control. As methodological procedures a qualitative research on the green infrastructure topic was adopted, having as spatial area the Tourist City of Tupã/SP (2005-2012 management). This way, when performing the case study proposed, the survey found and demonstrated the importance of incorporating green infrastructure in the process of urban planning and management, using the city of Tupã...